Competition Reform and Household Welfare: A Microsimulation Analysis of the Telecommunication Sector in Ethiopia - Carlos Rodriguez Castelan; Abdelkrim Araar; Eduardo A. Malásquez; Rogelio Granguillhome Ochoa (Institute of Labor Economics (IZA), 2021)
This paper presents a novel method for estimating the likely welfare effects of competition reforms for both current and new consumers. Using household budget survey data for 2015/16 for Ethiopia and assuming a reform scenario that dilutes the market share of the state-owned monopoly to 45 percent, the model predicts a 25.3 percent reduction in the price of mobile services and an increase of 4.6 million new users. This reform would generate a welfare gain of 1.37 percent among all consumers. Poverty rates are expected to decline by 0.31 percentage points, driven by a reduction of 0.22 percentage points for current consumers and 0.09 percentage points among new users. Inequality would increase by 0.23 Gini points since better off consumers are more likely to reap the benefits of greater competition. This method represents a powerful tool for supporting the analysis of competition reforms in developing countries, particularly in sectors known for excluding significant segments of the population due to high consumer prices.
Keywords: C15; D40; D60; I32; L86; N77; 330; competition reform; ICT; welfare effects; simulations; Ethiopia